Echinococcosis hydatid In The Central Sierra - Uceda del Campo, Jorge (1967)
Echinococcosis Hydatid disease caused by Echinococcus tapeworm larva is quite widespread in different areas of Peru. This study includes 383 cases filed in La Oroya for a period of 15 years and involves a surgical epidemiological study nosographic and disease, and its main objective to promote among government officials complete and final eradication of evil.